2009
DOI: 10.1111/j.1460-9592.2009.03136.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a low‐dose spinal morphine with bupivacaine for postoperative analgesia in children undergoing hypospadias repair

Abstract: Spinal anesthesia provided by hyperbaric bupivacaine is adequate for distal hypospadias repair in children, but adding 2 microg x kg(-1) intrathecal morphine provides better postoperative pain control when compared to placebo in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
3
7
0
3
Order By: Relevance
“…Epidural morphine (12–50mcg/kg) improves analgesia 9092 , and although early systemic absorption was detected, analgesia was evident 1 and 3 hours later when plasma levels were lower than required for a systemic analgesic effect 88 . Lower doses (2–5μg/kg) are effective intrathecally 9395 . The degree of dose sparing depends on the chemical properties of the drug, and for more lipophilic opioids such as fentanyl, the difference between equi-effective intrathecal, epidural and systemic doses may be less 96 .…”
Section: Clinical Choice Of a Spinal Analgesic: Efficacymentioning
confidence: 99%
“…Epidural morphine (12–50mcg/kg) improves analgesia 9092 , and although early systemic absorption was detected, analgesia was evident 1 and 3 hours later when plasma levels were lower than required for a systemic analgesic effect 88 . Lower doses (2–5μg/kg) are effective intrathecally 9395 . The degree of dose sparing depends on the chemical properties of the drug, and for more lipophilic opioids such as fentanyl, the difference between equi-effective intrathecal, epidural and systemic doses may be less 96 .…”
Section: Clinical Choice Of a Spinal Analgesic: Efficacymentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Kliniğimizde son on yıldır pediatrik olgularda spinal anestezi yöntemi giderek artan bir sıklıkta uygulanmakla beraber özellikle nö-romusküler hastalığı olan uygun pediatrik hastalarda ilk tercih edilen anestezi yöntemi olarak uygulanmaktadır. [2][3][4] Spinal anestezi uygulamasının pediatrik hastalarda tecrübeli ellerde genel anesteziye alternatif olarak güvenle kullanılabileceği çok sayıda yayında gösterilmiştir.…”
Section: Discussionunclassified
“…[2][3][4] Spinal anestezi uygulamasının pediatrik hastalarda tecrübeli ellerde genel anesteziye alternatif olarak güvenle kullanılabileceği çok sayıda yayında gösterilmiştir. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Pediatrik hasta grubunda erişkinlerden farklı olarak spinal anestezi uygulamalarının çoğu zaman sedasyon eşliğinde yapılması gerekmektedir. Sedasyon ile istemli ve istemsiz motor hareketler kontrol altına alınarak işlem esnasında uygulayıcı ve hasta konforu artırıldığı gibi aynı zamanda işlem güvenliği de artmaktadır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Currently, bupivacaine as a local anaesthetic and morphine to relieve pain are widely used in combination to provide effective postoperative analgesia. [4][5][6][7][8][9][10] However, the efficacy and safety of this combination for patients undergoing knee arthroscopic surgery remains controversial. Some studies found that IA bupivacaine plus morphine provided effective pain relief for patients, [11][12][13][14][15][16][17][18][19] while others did not.…”
Section: Introductionmentioning
confidence: 99%